Project Integration and Procurement Cultural Orientation and SME Growth: A Liberian Case Study - Ghuge, Sanket Suresh (Digital Repository of Theses - SSBM Geneva, 2025)
This case study explores the impact of project integration and procurement cultural orientation on the growth of small and medium-sized enterprises (SMEs) in Liberia. With a focus on the interplay between organizational practices and local cultural dynamics, the study examines how integrated project management approaches and culturally responsive procurement processes influence SME development in emerging markets. Drawing on qualitative data from Liberian SMEs and procurement entities, the research identifies key enablers and barriers to growth, including trust-building, capacity alignment, and policy coherence. The findings highlight the importance of culturally attuned integration strategies in fostering inclusive economic development and suggest policy recommendations for enhancing SME participation in national and donor-funded projects. Businesses in the food industry can improve their procurement processes, maintain a steady supply of high-quality ingredients, and stay competitive in an ever-evolving market by tackling these issues through strong supplier relationships, strict quality control, cost-effective strategies, technology-driven supply chain management, and sustainability initiatives. This study contributes to the broader discourse on sustainable development by providing context-specific insights into the relationship between project governance and entrepreneurial growth in post-conflict economies.